FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEMAMPUAN PASIEN DIABETES MELLITUS DALAM MENDETEKSI EPISODE HIPOGLIKEMI DI RSUD MARGONO SOEKARJO PURWOKERTO - Supadi, Supadi (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2011)
ABSTRACT Diabetes mellitus is a silent killer disease associated with hyperglycemia and insulin secretion falls below a critical amount or due to deficient action of insulin on metabolism. Hyperglycemia on diabetic patients is an acute complication of diabetes mellitus which may occur many times and deteriorate the disease and risk of death. This research was conducted to explore the effect of some factors that influenced the abilities of diabetic clients to detect hypoglycaemia episodic. This research used analytical descriptive with cross sectional study approach. The data was analyzed by Chi square. The result of study showed that there were no relationship between gender and the abilities of diabetic clients to detect hypoglycaemia (p:1,00), age (p:1.00), level of education (p:0.59), duration of diabetic (p:1.00), knowledge retention (p:0.32), and the availability of glucometer (p:1.00). In conclusion, there were no significant relationship between gender, level of education, duration of diabetic, knowledge retention, and the availability of glucometer and the abilities of diabetic clients to detect hypoglycaemia episodic. Keywords : hypoglicaemia,  diabetic  Kesmasindo. Volume 4,  Nomor 2, Juli 2011, hlm. 119-136